Multimodality management of borderline resectable pancreatic adenocarcinoma - Prakash, Laura R.; Katz, Matthew H. G. (Chinese Clinical Oncology, 2017)
Patients with borderline resectable pancreatic adenocarcinoma have primary tumors within the pancreas that involve the mesenteric vasculature to a limited degree. Their tumors are nonetheless at high-risk for a microscopically positive surgical resection margin and/or early treatment failure when pancreatectomy is performed de novo. The optimal treatment strategy for these patients has not been established; however, relatively favorable outcomes can be achieved with systemic chemotherapy and radiation therapy (RT) prior to intended resection. In this article, we discuss the modalities used to stage localized pancreatic cancer, the concept of borderline resectable pancreatic cancer (BRPC), the rationale for the use of preoperative therapy, and review recent publications, placing special emphasis on the necessity of appropriate patient selection and coordinating multimodality management to maximize outcomes.